Conversational Implicatures of Short Story in the Newspaper - Wiwien Pratiwi Harsa (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa, 2024)
Humans communicate using language, a medium that facilitates understanding in conversations, allowing individuals to connect and share information. This form of communication has evolved over time as people have interacted and engaged with one another. Within conversations, individuals often convey their intended meaning through indirect communication, a phenomenon that is explored through the lens of pragmatic concepts. The research conducted employed descriptive qualitative methods to delve into this aspect. By utilizing Grice’s implicature theory (1975) and the cooperative principle as frameworks, the study focused on observing and analyzing the various types of conversational maxims and implicatures in a short story from The Jakarta Post newspaper. The findings of the study revealed that the maxim of relevance was the most prevalent, accounting for approximately 43% of the instances, followed by the maxim of quality at around 33%, the maxim of manner at 19%, and the maxim of quantity at 5%. Additionally, it was noted that particularized conversational implicatures constituted 57.5% of the total, while generalized implicatures made up the remaining 42.5%. This research serves as a valuable resource for scholars and researchers in the field of linguistics, particularly those interested in exploring Grice’s implicature theory and its application to conversational implicatures. This study contributes to a deeper understanding of language use and interpretation by shedding light on the nuances of communication within written discourse.